(untitled) (International Journal of Engineering and Computer Science, 2016)
We think is that what we can access easily on the internet is whole of the information available. But actually the amount of information available is much larger in volume. Because the web is divided into two parts surface web which we can access easily and the deep web which is invisible to us as the search engines are unable to index it directly. To handle this huge volume of information, Web searcher uses search engines. But hidden web contains a large collection of data that is unreachable by normal hyperlink-based search engines. To access this content, one must submit valid input values to the HTML form. The resultant web pages from the previous step are stored and then to improvise the search results for a user query we need indexing techniques. Indexing of hidden web is done to reveal the relevance of the document according to the context of the search. The objective is to find out different ways for indexing the web pages from the hidden web using ontology and analyze the different techniques that are previously proposed. The main advantage of storing an index is to optimize the speed and performance while finding relevant documents from the search engine storage area for a user given search query.